Assessment of psychometric properties and measurement invariance of the sensation seeking scale for children in a Norwegian sample - Sandseter, Ellen Beate Hansen; Sando, Ole Johan; Kleppe, Rasmus; Lorås, Håvard; Storli, Lise (Frontiers in Psychology, 2024)
The aim of this study was to examine the psychometric properties of a Norwegian translation of the Sensation Seeking Scale for Children (SSSC), designed for children between 7 and 12 years of age. A sample of 393 children (7-10 years old) were recruited to participate in the study. The SSSC was administered through interviews with each child, wherein their responses to the SSSC questionnaire were recorded on a tablet. Analysis of internal consistency reliability did not show acceptable reliability for all subscales, and confirmatory factor analysis (CFA) showed that the Thrill Seeking and Behavioral Intensity subscales were associated and somewhat overlapping, while Behavioral Inhibition appeared as a single factor. A further explanatory factor analysis (EFA) revealed a twofactor solution. CFA of the two-factor solution resulted in the removal of some items in both factors due to low factor loadings. The final factors resulting from this analysis were Thrill and Intensity Seeking (13 items) and Behavioral Inhibition (7 items). The results also show that boys scored higher than girls on Thrill and Intensity Seeking while girls scored higher than boys on Behavioral Inhibition. Furthermore, age was positively associated with both subscales, meaning that older children tended to score higher. The results in this study suggest that measures of children's sensation seeking might be sensitive to cultural contexts and that, at least in a Norwegian population, a twofactor solution of the SSSC is recommended.